Employee engagement and innovative work behavior: The mediating role of knowledge-sharing behavior in the United Arab Emirates (UAE) service context - Abdallah M. Elamin; Hazem Aldabbas; Ahmed Zain Elabdin Ahmed; Abdulaziz N. Abdullah (Administrative Sciences, 2024)
The aim of this study was to examine the mediating role of knowledge-sharing behavior (KSB) in the relationship between employee engagement and innovative work behavior (IWB). We collected 193 completed survey responses from employees working in the service sector in the United Arab Emirates (UAE). Drawing on social exchange theory (SET), we employed hierarchical regression to analyze the research framework and the mediation effect. The primary findings indicate a significant positive association between employee engagement and IWB, as well as between employee engagement and KSB. Additionally, there is a significant positive association between KSB and IWB. Furthermore, employee engagement has an indirect effect on IWB via the mediating role of KSB. We recommend further research and practical investigation into how employee engagement contributes to enhancing knowledge-sharing behavior and IWB, ultimately improving organizational performance.
Keywords: 350; employee engagement; innovative work behavior (IWB); knowledge-sharing behavior (KSB); social exchange theory; United Arab Emirates (UAE)